Increasing Gain Evaluation of 2×1 and 2×2 MIMO Microstrip Antennas - Dwairi, M. O. (Engineering, Technology & Applied Science Research, 2021)
In this paper, a semi-circular ultra-wideband antenna has been modified according to the 2×1 and 2×2 MIMO scenarios. The proposed antennas were designed based on the FR-4 substrate material with dimensions of 36×50mm and 60×60mm for 2×1 and 2×2 scenarios respectively. Simulation results show that a gain improvement of the proposed MIMO antennas from 1 to 2.5dB has been achieved in comparison with the single patch antenna. The radiation pattern for the original and the proposed 2×2 MIMO antennas are exhibited. The main advantage of the proposed antennas is that the gain improves without the need to increase the operating power. This makes the proposed MIMO antennas suitable to be used for UWB antenna applications.